Experimental Evaluation of Low-Density Polyethylene by Pyrolysis Route - Ravindra Pathak , Serajul Haque, Amrutrao (International Journal of Advanced Science and Technology, 2020)
This research is focused on the pyrolysis of waste polymers in order to obtain oily fractions having similar performances compared to the products conventional. This process results mainly from large distributions of hydrocarbons which require further treatment (distillation, hydrogenation) to obtain valuable products. This research shows the experimental development of the pyrolysis process, carried out in a closed batch type reactor, where the production of liquid hydrocarbons from plastic waste from Low-Density Polyethylene (LDPE)in the temperature range from 300 °C to 500 °C. Furthermore, the hydrocarbons obtained were characterized to obtain their physico-chemical properties with experimental tools used in the development of this work.